2009
DOI: 10.1158/0008-5472.can-09-1601
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the Carney Complex Gene 1 (Protein Kinase A Regulatory Subunit 1A) Inhibits SMAD3 Expression and TGFβ-Stimulated Apoptosis in Adrenocortical Cells

Abstract: The cyclic AMP signaling pathway can be altered at multiple levels in endocrine tumors. Its central component is the protein kinase A (PKA). Carney complex (CNC) is a hereditary multiple neoplasia syndrome resulting from inactivating mutations of the gene encoding the PKA type I A regulatory subunit (PRKAR1A). Primary pigmented nodular adrenocortical disease is the most frequent endocrine tumor of CNC. Transforming growth factor B (TGFB) regulates adrenal cortex physiology and signals through SMAD2/3. We used … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 48 publications
3
37
0
3
Order By: Relevance
“…Increased gregarization after RNAi against pkar1 derives from the inhibitory function of R subunits in regulating catalytic activity. In the absence of cAMP, C and R subunits assemble into inactive R 2 C 2 complexes; active C subunits are released upon binding of cAMP to R. In this equilibrium reaction, a decreased R:C ratio leads to the release of more catalytic activity for a given concentration of cAMP (46), as recently demonstrated by RNAi against PKAR1A in HEK293 cells (45). In Aplysia neurons, 5-HT induces cleavage of the R1 subunit but not the R2 subunit (47).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Increased gregarization after RNAi against pkar1 derives from the inhibitory function of R subunits in regulating catalytic activity. In the absence of cAMP, C and R subunits assemble into inactive R 2 C 2 complexes; active C subunits are released upon binding of cAMP to R. In this equilibrium reaction, a decreased R:C ratio leads to the release of more catalytic activity for a given concentration of cAMP (46), as recently demonstrated by RNAi against PKAR1A in HEK293 cells (45). In Aplysia neurons, 5-HT induces cleavage of the R1 subunit but not the R2 subunit (47).…”
Section: Discussionmentioning
confidence: 90%
“…Degradation of the R subunits can then result in sustained PKA activity that outlasts the cAMP signal (44). RNAi against PKAR1A has recently been found to increase basal and stimulated PKA activity in HEK293 cells (45). We reasoned that, if PKA were the effector of a gregarizing 5-HT signal, RNAi against R1 might induce a shift toward increased gregariousness.…”
Section: Reduction In Pka C1 Subunit Expression Correlates With Reducedmentioning
confidence: 99%
“…Elevation of ALK7 by induction with adenovirus-carrying expression vector coding for active ALK7 resulted in a remarkable inhibition of ␤-cell proliferation and the acceleration of ␤-cell apoptosis (64). In the ␤-cells, activation of ALK7-induced inhibition of cell proliferation and increased apoptosis appeared to be mediated by the Smad2-caspase-3 signaling pathway(s), as demonstrated in many other cell lineages (30,41,46,63), and the suppression of Akt activation (64). Previous in vitro and in vivo studies showed that activins or Nodal may interact with ALK7 to exert downstream events (7,27,41,47).…”
mentioning
confidence: 95%
“…We have investigated the regulation of 5-HTR expression in PPNAD by using the PRKAR1A-mutated PPNAD CAR47 cell line (32), which expressed HTR4 and HTR7 mRNAs but not the HTR6 mRNA (Figure 4, A Inhibition of PRKAR1A expression triggers expression of a serotonergic loop in the human adrenocortical cell line H295R. Previous investigations have shown that PRKAR1A silencing increases total PKA activity in adrenocortical H295R cell lines (33), as observed in PPNAD cells. In order to confirm that activation of the cAMP/PKA pathway upregulates TPH2 and HTR4/6/7 gene expression, we have used the human adrenocortical cell line H295R to generate cell clones expressing a doxycyclin-inducible (Dox-inducible) shR-NA targeted to PRKAR1A mRNA.…”
Section: Involvement Of 5-ht 4/6/7 Receptors In the Stimulatory Effecmentioning
confidence: 99%